Dolphin Morbillivirus Infection in a Captive Harbor Seal (Phoca vitulina). - MAZZARIOL, SANDRO; Peletto S; MONDIN, ALESSANDRA; CENTELLEGHE, CINZIA; Di Guardo G; Di Francesco CE; Casalone C; Acutis PL (Journal of Clinical Microbiology, 2013)
During the second morbillivirus epidemic (2007 to 2011) in cetaceans along the Italian coastline, dolphin morbillivirus (DMV) was detected by molecular analyses in a captive harbor seal (Phoca vitulina), with pathological findings consistent with morbilli- virus infection. This report confirms interspecies DMV transmission from cetaceans to pinnipeds.